Carbon, Nitrogen, Phosphorus, and Potassium Content Partitioning of Cocoa Tree Parts in Serian, Sarawak (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
Many claim that commodity plantations release carbon stock and thus contribute to climate change effects. Yet, studies on cocoa carbon stock and nutrients are limited, especially in Malaysia therefore, objective of this study was to determine if there were any significant differences of carbon stock in five different tree parts of cocoa, namely branches, main stem, main roots, fibrous roots, and leaves. Twenty cocoa trees (aged 10 years old) at Kpg Muara Ahi, Serian Sarawak were destructively sampled in March, 2016, and cut into five tree compartments prior to analysis by using CHN and AAS Analyzer. Mean comparison was carried out by using one-way ANOVA SPSS 21.0 software. Total cocoa carbon stock was 27.32 M C ha -1 which branches contributing 47% from the total carbon (12.92 Mg C ha -1 ), followed by main stem (5.42 Mg C ha -1 ), taproot (4.05 Mg C ha -1 ), fibrous root (2.49 Mg C ha -1 ) and leaves (2.44 Mg C ha -1 ). Branches and main stems contained higher total carbon stock due to high total biomass (kg), how-ever, main root showed significantly (p